Development of Digital Comic Learning Media in Social Studies Subjects for Grade IV Students of SDN Kalibaru 07 - Jeannisari Amalia Miftahul Jannah; Muhib Rosyidi (Budapest International Research and Critics University, 2022)
This research was carried out based on the results of field analysis to teachers regarding the difficulties in developing learning media so that they felt bored during the learning process. This study aims to develop digital comics learning media in social studies subjects for economic activities. The method used in this research is the development (R&D) method with the ADDIE model which consists of four steps, namely 1) analysis, 2) design, 3) development, 4) implementation and 5) evaluations. This research was conducted at SDN Kalibaru 07. The information obtained in this study was conducted by giving questionnaires to media experts, material experts, education experts, and questionnaires from students.